The environmentalism of the poor a study of ecological conflicts and valuation - Martinez-Alier, Joan.; Edward Elgar Publishing (Northampton, Mass. : Edward Elgar Pub., 2002)
The Environmentalism of the Poor has the explicit intention of helping to establish two emerging fields of study--political ecology and ecological economics--whilst also investigating the relations between them.
1. Currents of environmentalism -- 2. Ecological economics : "taking nature into account" -- 3. Indices of (un) sustainability, and neo-Malthusianism -- 4. Political ecology : the study of ecological distribution conflicts -- 5. Mangroves versus shrimps -- 6. The environmentalism of the poor : gold, oil, forests, rivers, biopiracy -- 7. Indicators of urban unsustainability as indicators of social conflict -- 8. Environmental justice in the United States and South Africa -- 9. The state and other actors -- 10. The ecological debt -- 11. On the relations between political ecology and ecological economics.
Includes bibliographical references and index.
Keywords: Environmental economics; Environmental policy; Economic development -- Environmental aspects; Electronic books